Weed population and growth performance of aerobic rice (AERON 1) under different type of fertilizer / Ahmad Arrmi Yahya - Yahya, Ahmad Arrmi (Faculty of Plantation and Agrotechnology, 2019)
Rice is the most important crop in agriculture and served as the staple food for million people especially in the Asia Pacific region. The area of rice cultivation increases due to increasing of world populations over years. In the meantime, the productivity of rice is highly threatened by physical water scarcities that are facing globally. Thus, development of new production rice system namely aerobic rice seems to be as the solution for this problem since its can be cultivated under non puddled and non-saturated condition without necessity for standing water in field unlike flooded rice. However, weed infestation was found as major limitation in aerobic rice production due to no standing water to supress weed germination. This study was conducted with the aims to identify weed population and plant performance of aerobic rice (AERON 1) with different types of fertilizer. Experiment was arranged in RCBD with 3 replications involved 4 treatments consist of NPK, chicken dung, effective microorganism (EM) and EM mixed with chicken dung. Based on the data collection, the most dominance weed emerge on the sample is Leptochloa chinensis from grasses class. Plant growth performance seems that treatment consist of EM content were at par with NPK fertilizer performance. Thus, plant growth performance under treatment consist of EM content can be consider as the other alternative or substitutes to the chemical fertilizer.